Use of external solar spectra to multispectral sensor systems as an alternative for radiometric correction and calibration of ToA reflectance - Müller, Jonathan Gil; Vibrans, Alexander Christian (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
Most Earth observation satellite missions do not have instruments to measure solar irradiance in orbit. Consequently, the temporal variability of the recorded reflectance is based only on the radiance measured by the sensor, since the incident solar irradiance is considered constant. This approach neglects non-seasonal variability associated with solar activity and can compromise the accuracy of reflectance values. The aim of this study was to investigate if solar spectra obtained daily by instruments external to multispectral sensor systems can contribute to increasing the accuracy of top-of-atmosphere (ToA) reflectance data. Solar spectra from the Spectral Irradiance Monitor (SIM/SORCE) instrument and ToA reflectance data from the Enhanced Thematic Mapper Plus (ETM+/Landsat-7) sensor were used. ToA reflectance data from the Radiometric Calibration Network portal was used as a reference for the accuracy analysis. The results indicate that the use of SIM/SORCE solar spectra in the radiometric correction of ETM+/Landsat-7 ToA reflectance can help increase the accuracy rates of ToA reflectance in the green (> 1%), red (> 0.1%), NIR (> 0.1%), SWIR-1 (> 3%) and SWIR-2 (> 2%) spectral bands. In addition, contributions to temporal stability were found in the blue, green, NIR and SWIR-1 bands (< 0.2%). We conclude that the use of external daily solar spectra can contribute to improving the accuracy and temporal stability of ToA reflectance values obtained by multispectral sensor systems whose pre-processing is based on radiance values.